Cost-Effectiveness Analysis of Pembrolizumab Plus Pemetrexed and Platinum Versus Chemotherapy Alone as First-Line Treatment in Metastatic Non-Squamous Non–Small Cell Lung Cancer: A Reconstruction of Partitioned Survival Model Based on Time Dependent Pricing Mechanism of Patient Assistance Program - Cai, Yuanyi; Hui, Wen; Zhu, Min; Zhang, Mingyue; Gao, Zhixiang; Wu, Huazhang (Frontiers in Oncology, 2021)
Objectives: A new patient assistance program (PAP) for pembrolizumab was started in China in 2021. The researchers aimed to evaluate the economic outcomes of pembrolizumab plus pemetrexed and platinum versus chemotherapy alone in the first-line treatment of patients with metastatic non-squamous non-small cell lung cancer, based on the pricing mechanism of PAP. Material and Methods: Survival analysis and partitioned survival model were performed to evaluate the incremental cost-effectiveness ratio (ICER) in the pembrolizumab group compared with the chemotherapy group. Survival probabilities were extracted from the data of the KEYNOTE-189 trial. Cost and utility data were gathered from published literature. The pricing mechanism of PAP was set in each cycle in the partitioned survival model, according to the progression-free survival (PFS) data of the KEYNOTE-189 trial, which included PFS-1 and PFS-2. Deterministic sensitivity analysis and probabilistic sensitivity analysis were conducted. Results: The ICER of the pembrolizumab group versus chemotherapy group was $65,272/quality-adjusted life year (QALY), which still exceeded the willingness-to-pay threshold of three times per capita gross domestic product (GDP) of China ($33,581.22), although PAP was calculated. Sensitivity analysis implied that the price of chemotherapeutic drugs combined with pembrolizumab was one of the main influencing factors of ICER. Conclusions: Due to various prices set by PAP and the payment for combined chemotherapy, the economic advantage of pembrolizumab plus chemotherapy in the first-line treatment of non-small cell lung cancer (NSCLC) is still not achieved in China.